TCAD Simulation and Analysis of Selective Buried Oxide MOSFET Dynamic Power - Mahmoud, Rana (2019)
Low power consumption has become one of the major requirements for most microelectronic devices and systems. Increasing power dissipation may lead to decreasing system effciency and lifetime. The BULK metal oxide semiconductor field-effect transistor (MOSFET) has relatively high power dissipation and low frequency response due to its internal capacitances. Although the silicon-on-insulator (SOI) MOSFET was introduced to resolve these limitations, other challenges were introduced including the kink effect in the current-voltage characteristics. The selective buried oxide (SELBOX) MOSFET was then suggested to resolve the problem of the kink effect. The authors have previously investigated and reported the characteristics of the SELBOX structure in terms of kink effect, frequency, thermal and static power characteristics. In this paper, we continue our investigation by presenting the dynamic power characteristics of the SELBOX structure and compare that with the BULK and SOI structures. The simulated fabrication of the three devices was conducted using Silvaco TCAD tools in 90 nm complementary metal oxide semiconductor (CMOS) technology. Simulation results show that the average dynamic power dissipation of the CMOS BULK, SOI and SELBOX are compatible at high frequencies with approximately 54.5 μW. At low frequencies, the SOI and SELBOX showed comparable dynamic power dissipation but with lower values than the BULK structure. The difference in power dissipation between the SELBOX and BULK is in the order of nano watts. This power difference becomes significant at the chip level. For instance, at 1 MHz, SOI and SELBOX exhibit an average dynamic power consumption of 0.0026 μWless than that of the BULK structure. This value cannot be ignored when a chip operates using thousands or millions of SOI or SELBOX MOSFETs.